MEDIA AUDIO VISUAL AKUATIK UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN RENANG - Ermawan Susanto (PAEDAGOGIA, 2010)
The aim of this classroom action research is to improve the quality of aquaticlearning for FIK undergraduate student. The samples of research are sixty D-II PGSDphysical education program. The research methods used are descriptive analytictechnique and analytic data process consisting of: (1) describing data, (2) validity ofdata, and (3) interpretation of data. The steps of research process are: (1) preparation,(2) process: planning, acting, observing, reflecting, (3) conclusion. The acting preparationsof the research are three cycles. The result of that audio visual can improve theresearch showed quality of aquatic learning for D-II PGSD physical education program.In the first and second cycle, the qualities of aquatic learning were still low. The thirdcycle, the qualities of aquatic learning were improve by playing compact disk audiovisual of kind of swimming.